The influence of cold rolling and hydroxyapatite coating on the mechanostructure, corrosion resistance, cell viability, and antibacterial activity of ZnCu biodegradable implants - Aksakal, B.; Karadogan, S. A.; Aslan, N.; Fidan, F.; Yilmazer, Y.; Sezek, S. (Springer Heidelberg, 2024)
Zinc (Zn) and its alloys exhibit great potential for utilization in biodegradable bone implants. Zn-1Cu biodegradable alloy was produced and were cold rolled at two different deformation rates of 47 and 61%. The samples have been bioceramic coated with the sol-gel method and microstructure-mechanical property changes, corrosion behavior and biocompatibility of the samples were investigated. They were characterized by Optical, SEM, XRD and wettability analysis. The rolled samples showed a significant increase in hardness when compared to the non-rolled samples. The unrolled and 47% rolled samples showed better corrosion resistance compared to 61% rolled samples. Antibacterial effects of the base and sol-gel-coated groups showed higher cell viability ratios than the uncoated groups. Cell viability increased significantly in 47% of the rolled samples after 24, 48, and 72 h, however decreased by up to 70% in 61% of the rolled samples.
Keywords: Antibacterial activity; Biodegradable implants; Cell viability; Corrosion; Rolling; Sol-gel